Voices From the Edge: Lived Experiences of Male Vulnerable Children - Marissa L. Lontoc; Yna Angelie T. Erestain; Princess Nicole B. Lucero; Sharmaine A. Panganiban (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study explored the lived experiences of male vulnerable children in Cavite, Philippines, particularly those classified as Children in Conflict with the Law (CICL), who were exposed to adverse family, social, and economic conditions. It specifically aimed to examine the underlying causes of their misbehavior and to identify the coping strategies they employed prior to and during institutionalization. Using a qualitative phenomenological design, three male adolescent aged 16-18 residing in a Bahay Pag-asa were purposively selected based on gender, age, length of institutional stay, educational attainment, and family background. Data were gathered through semi-structured interviews, transcribed verbatim, and analyzed using thematic analysis. Findings revealed interconnected themes including problems at home, delinquent behavior with peers, financial constraints, boredom during rehabilitation, repentance, and self-reflection. These experiences highlighted coping strategies such as seeking belonging through peer affiliation, economic coping through informal or illegal means, avoidance behaviors (e.g., running away), and adaptive coping through reflection and repentance during intervention. The findings underscore the importance of gender-responsive and context -specific interventions to support the rehabilitation and reintegration of male adolescents in institutional care.